450 d of Type II SN 2013ej in optical and near-infrared. Issue 2 (15th June 2016) - Yuan, Fang; Jerkstrand, A.; Valenti, S.; Sollerman, J.; Seitenzahl, I. R.; Pastorello, A.; Schulze, S.; Chen, T.-W.; Childress, M. J.; Fraser, M.; Fremling, C.; Kotak, R.; et al.
Abstract: We present optical and near-infrared photometric and spectroscopic observations of SN 2013ej, in galaxy M74, from 1 to 450 d after the explosion. SN 2013ej is a hydrogen-rich supernova, classified as a Type IIL due to its relatively fast decline following the initial peak. It has a relatively high peak luminosity (absolute magnitude M V = −17.6) but a small 56 Ni production of ∼0.023 M⊙ . Its photospheric evolution is similar to other Type II SNe, with shallow absorption in the H α profile typical for a Type IIL. During transition to the radioactive decay tail at ∼100 d, we find the SN to grow bluer in B  −  V colour, in contrast to some other Type II supernovae. At late times, the bolometric light curve declined faster than expected from 56 Co decay and we observed unusually broad and asymmetric nebular emission lines. Based on comparison of nebular emission lines most sensitive to the progenitor core mass, we find our observations are best matched to synthesized spectral models with a M ZAMS  = 12–15 M⊙ progenitor. The derived mass range is similar to but not higher than the mass estimated for Type IIP progenitors. This is against the idea that Type IIL are from more massive stars. Observations are consistent with the SN having a progenitor with a relatively low-mass envelope.